Pediatric leukodystrophies: The role of the otolaryngologist. (October 2017) - Kay-Rivest, Emily; Khendek, Léticia; Bernard, Geneviève; Daniel, Sam J.
Abstract: Background: Leukodystrophies consist of degenerative neurogenetic diseases often associated with comorbidities that extend beyond the neurological system. Despite their impacts on patients' quality of life and risks of complications, head and neck symptomology is poorly reported in the literature. The objective of this study was to identify and quantify the main head and neck complaints among a cohort of patients diagnosed with leukodystrophies and define the role of the otolaryngologist as part of a multidisciplinary team for treating these patients. Methods: During the First Canadian National Conference on Leukodystrophies held at the Montreal's Children Hospital, a cohort of 12 patients diagnosed with leukodystrophies were recruited and evaluated by a multidisciplinary team. An otolaryngology-focused assessment was done through history and physical examination, and included a screening questionnaire for 23 common otolaryngology issues. If families reported a history of sialorrhea, a validated questionnaire (Drool Quality of Life Assessment Questionnaire (DroolQoL)) was subsequently distributed. Results from the questionnaires were then compiled and analyzed. Results: Of the 12 recruited patients, 83% (10/12) were known to an otolaryngologist. Drooling affected 67% (8/12) of patients although only 37.5% (3/8) of patients had undergone medical or surgical therapies for this issue. Four patients experienced at least one aspiration pneumonia. 58% (7/12) of the patients had dysphagia, of whom 43% (3/12) were fed exclusively via gastrostomy tube and 28% (2/7) required thickening of feeds. Two patients, despite suspicion of dysphagia and aspiration, had never undergone evaluation. As for otologic issues, it was noted that 25% (3/12) of patients had a history of pressure equalizing tubes (PETs) and one patient had a history of hearing loss. Conclusion: Head and neck comorbidities affect children with leukodystrophies. Therefore, the otolaryngologist should be part of the multidisciplinary team, specifically for the management of dysphagia and sialorrhea.